Analisis Pesan Moral Dalam Film “ Cinta Subuh ” Di TV Berlangganan Disney+ Hotstar - Muhammad Rafi Atha Dhiya; Harmonis Harmonis (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Moral messages themselves contain sees on the qualities and standards that exist among a gathering. Virtues are the decency of people as people. Standards about how people should live to be great as people. Films are amusement, yet in addition data and training media, conveying data through motion pictures should be possible rapidly. This exploration expects to figure out the ethical message contained in the film Cinta Subuh. This exploration utilizes Roland Barthes' semiotic examination hypothesis, to be specific signification meaning, implication importance, and legend contained in the film Cinta Subuh. The examination area was directed on the advanced membership TV stage, Disney+ Hotstar. This examination strategy utilizes a subjective technique, which is an exploration system that produces enlightening information as composed or expressed words from individuals and ways of behaving that can be taken. The consequences of this study demonstrate that there are a few moral messages, specifically: counsel not to date, lying is a wrongdoing in any event, for goodness, focusing on morning supplications as an impression of life and the figure of kinship supporting the great way. In this unique situation, there is an end from this film that underlines the significance of trustworthiness in close connections. Genuineness is a general worth perceived in many societies and convictions.